2015
DOI: 10.1542/peds.2015-2776ff
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Peanut Consumption in Infants at Risk for Peanut Allergy

Abstract: Background-The prevalence of peanut allergy among children in Western countries has doubled in the past 10 years, and peanut allergy is becoming apparent in Africa and Asia. We evaluated strategies of peanut consumption and avoidance to determine which strategy is most effective in preventing the development of peanut allergy in infants at high risk for the allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To elucidate the role of CF in the development of allergies, several studies have demonstrated that early and repeated exposure to an antigen during critical windows leads to optimal development of immunotolerance [66]. As a consequence, regimens currently recommended by several National Institutes of Health actively encourage the early introduction of potential common food allergens, such as peanut and egg, at approximately 6 months of age, but not before 4 months of age [67].…”
Section: Allergymentioning
confidence: 99%
“…To elucidate the role of CF in the development of allergies, several studies have demonstrated that early and repeated exposure to an antigen during critical windows leads to optimal development of immunotolerance [66]. As a consequence, regimens currently recommended by several National Institutes of Health actively encourage the early introduction of potential common food allergens, such as peanut and egg, at approximately 6 months of age, but not before 4 months of age [67].…”
Section: Allergymentioning
confidence: 99%